Anemia Pada Karsinoma Kolorektal: Hubungan Dengan Lokasi Tumor di Rumah Sakit Umum di Aceh - Cut Balqis Ammara; Muhammad Sayuti; Khairunnisa Z (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Cancer of the large intestine (colon) and/or rectum is medically referred as colorectal carcinoma. Colorectal cancer patients' clinical symptoms can vary depending on where the tumor is located. A low red blood cell (RBC) count, hemoglobin (Hb), or hematocrit (HCT) indicates anemia. The purpose of this research is to examine whether or not individuals with colorectal cancer have a higher risk of anemia depending on where their tumors are located. Method: Cross-sectional observational analysis was used as the research method. Colorectal cancer patients diagnosed at Cut Meutia General Hospital in 2020-2021 served as research subjects. The inclusion and exclusion criteria were met by 40 people. The chi-square test is used to validate information in a patient's medical record about Hb levels obtained from standard blood laboratory testing in colorectal cancer patients. Results: The majority of patients in this study were male (62.5%), between the ages of 40 and 50 (mean 45.5), with the main complaint being bloody stools in 14 patients (40%), tumor location left colon in 35 patients (87.5%), and mild anemia in 19 (47.5%). Three patients (60%) had severe anemia in the right colon, while 18 patients (94.7%) had moderate anemia in the left colon. Colorectal cancer patients have an increased risk of anemia based on tumor location (=0.003). Conclution: Patients with colorectal cancer treated at Cut Meutia General Hospital, North Aceh, in 2020–2021 were shown to have a strong correlation between tumor site and anemia severity.